STUDI EFEK PEMODELAN STRUKTUR TANGGA PADA BANGUNAN RUKO 3 TINGKAT AKIBAT BEBAN GEMPA - Agus Subrianto (Politeknik Negeri Sriwijaya, 2023)
ABSTRAct In designing buildings such as shophouses, the staircase structure is often modeled as a load and calculated separately from the structure. In this study, the effect of staircase modeling on the structure is reviewed by observing 3 conditions, namely: 1) the staircase structure is defined as a line load on the floor beam directly,2) part of the staircase load is included on the landing beam, and 3) the stairs are modeled as a complete structure into the building. The building is located on soft soil and is categorized as SDC D. The structure consists of 3 levels with 4 door buildings. The structures are modeled in 3 dimensions, using the lateral equivalent static earthquake procedure. The results show that modeling the stairs as a structure can increase the stiffness up to 41.82%, reduce the period of vibration up to 12.06%, the base shear force increases 3.41%, overturning moment up to 6.56%, the inter story drift and the stability coefficient is smaller, the shear force on the column supporting the stairs increased very significantly to 268.63% on the major axis and up to 405.92% on the minor axis. Keywords : Staircase structure, shophouse building, stiffnes, shear force